2014
DOI: 10.1093/gerona/glu110
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Function Response to Clinical Interventions of Older Women Categorized by Weakness and Low Lean Mass Using Classifications From the Foundation for the National Institute of Health Sarcopenia Project

Abstract: Older women with clinically meaningful muscle weakness increased grip strength and SPPB, regardless of the presence of low lean mass following treatment with interventions for frailty. Thus, results suggest that muscle weakness, as defined by the Foundation for the National Institutes of Health Sarcopenia Project, appears to be a treatable symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 51 publications
1
37
0
2
Order By: Relevance
“…Positive treatment effects among these frailty constructs may partially explain why pulmonary rehabilitation improves exercise capacity, disability, and health-related quality of life and reduces hospitalizations and mortality 106,107. Recent work in older populations has shown that frailty may be reversible through targeted exercise and nutritional interventions 108110. It has been postulated that nutritional interventions may be suitable for frail patients with nutritional deficiency and weight loss; however, the evidence for this has been scarce.…”
Section: Interventionmentioning
confidence: 99%
“…Positive treatment effects among these frailty constructs may partially explain why pulmonary rehabilitation improves exercise capacity, disability, and health-related quality of life and reduces hospitalizations and mortality 106,107. Recent work in older populations has shown that frailty may be reversible through targeted exercise and nutritional interventions 108110. It has been postulated that nutritional interventions may be suitable for frail patients with nutritional deficiency and weight loss; however, the evidence for this has been scarce.…”
Section: Interventionmentioning
confidence: 99%
“…Recent work in older populations shows that frailty may be reversible through targeted exercise and nutrition interventions (11,98,99). That muscle wasting, weakness, and malnutrition (hallmarks of frailty) are common in those with lung disease and should be responsive to physical exercise training and nutrition optimization underscores the importance of rehabilitation.…”
Section: Frailty As a Therapeutic Target In Pulmonary Disease And Crimentioning
confidence: 99%
“…Muscle quality (MQ) can be conceptualized as the capacity to generate force relative to the mass/volume of contractile tissue (13). Declines in muscle strength with aging are not explained by declines in muscle mass; the concept of MQ was meant to describe this phenomenon (1, 2, 46).…”
Section: Introductionmentioning
confidence: 99%
“…While strength alone quantifies the amount of force a muscle can generate, bigger muscles are not necessarily stronger. A smaller muscle may be more effective due to more contractile proteins, less fat infiltration, or other physiological properties that can alter the quality of the muscle (3, 6, 7). Therefore, MQ could be useful to comprehensively quantify physiological changes in skeletal muscle that occur with aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation